(untitled) (Iraqi Journal of Medical Sciences, 2016)
The gold standard method for nerve reconstruction involve the use of autologous graft, however, major drawbacks included limited availability, donor-site morbidities and requirement of multiple surgeries. Researchers worldwide had aimed to produce alternative tissue-engineered synthetic nerve conduits, but development had been slow, with only four FDA (US Food and Drug Administration) approved conduits for human subjects in the past 50 years of research. This slow progress may potentially be related to the lack of standardized guideline for nerve conduit testing. This review aims to summarize the methodologies used in the testing of nerve conduits in vivo and in vitro. The review demonstrated a lack of consensus and consistency in the study methodologies, including various measures of functional assessment, over 8 different types of animal species, 17 peripheral nerves and varied gap lengths ranging between 1 mm and 90 mm. In vitro models demonstrate more consistencies in testing models, but have been discarded in recent years for functional nerve testing, and had been employed for preliminary testing in nerve toxicity and compatibility instead. This study emphasizes the urgent need for a more standardized approach for in vivo testing, and the need to re-utilize in vitro studies for functional testing purposes. Key words: nerve conduits; tissue engineering; peripheral nerves; testing methodology